Association between atopic disorders and mental ill health: a UK-based retrospective cohort study - Joht Singh Chandan; Nicola Adderley; Rebecca Knibb; Lavanya Diwakar; Sonica Minhas (BMJ Open)
Objective To examine the mental ill health burden associated with allergic and atopic disorders, in a UK primary care cohort.Design Population-based retrospective open cohort study.Setting United Kingdom.Participants 2 491 086 individuals with primary-care recorded atopic disorder (food allergy, drug allergy, anaphylaxis, urticaria, allergic rhino-conjunctivitis) diagnosis were matched by sex, age (± 2 years), and socio-economic deprivation (Townsend quintile score) at index to 3 120 719 unexposed individuals. The mean age of exposed patients at cohort entry was 39.42 years (SD (SD) 23.65) compared with 35.81 years (SD 22.17) for unexposed patients.Main outcome measures The primary outcome was a composite of mental ill health (severe mental illness, anxiety, depression, eating disorders, obsessive-compulsive disorder (OCD), and self-harm), identified using Read codes. Cox regression was used to estimate adjusted hazard ratios with 95% confidence intervals for the composite mental ill health outcome and each of the individual mental health disorders. Covariates adjusted for were age, sex, alcohol use, smoking status, body mass index (BMI), Townsend deprivation quintile score, asthma exposure, and eczema exposure at baseline.Results Between first January 1995 to 31st January 2022, a total of 2 491 086 eligible individuals were identified with a primary care recorded diagnosis of atopic disease and were matched to 3 120 719 unexposed individuals. 229 124 exposed individuals developed a mental ill health outcome during the study period (incidence ratio (IR) 144.13 per 10 000 person-years) compared with 203 450 in the unexposed group (IR 117.82 per 10 000 person-years). This translated to an adjusted hazard ratio (aHR) of 1.16 (95% CI 1.15 to 1.17). Notably, the risk of anxiety was greatest, aHR 1.22 (95% CI 1.21 to 1.23). Our findings were robust to a sensitivity analysis, where individuals were also matched for asthma and eczema.Conclusion There is an increased risk of mental ill health disorders among patients with diagnosis of an allergic and atopic disorders. There is a need to consider dual delivery of allergy and psychology services to optimise mental well-being among this cohort.